Coping Strategies during Childbirth Related to Cultural Identity: Companionship, Choice of Analgesia and Maternal Satisfaction. - Navarro-Prado, Silvia; Sánchez-Ojeda, María Angustías; Plaza del Pino, Fernando Jesús; Vázquez-Sánchez, María Ángeles; Tovar-Gálvez, María Isabel; Azirar-Mohamed, Nurimán (MDPI, 2023)
Childbirth is a biological process and how it is experienced and managed is influenced by numerous factors, among them, socio-cultural or health care received. Objective: The objective of this study is to ascertain whether cultural factors influence the way in which women deal with childbirth through the treatment of pain, companionship and maternal satisfaction. Methods: This study is a non-experimental, quantitative, ex post facto, cross-sectional study of women who gave birth in a border town in southern Spain. The sample consisted of 249 women. Results: No relationship was found between cultural factors and the choice of epidural analgesia, alternative methods to alleviate pain, being accompanied nor maternal satisfaction. There was a significant relationship between the type of companionship and with maternal satisfaction. Conclusions: Cultural factors did not influence how women dealt with dilation and childbirth. Results found that the person accompanying the mother was important for increasing maternal satisfaction. The intercultural training of healthcare professionals is necessary.
Keywords: Analgesia; Parto - Aspectos culturales; Childbirth; Patient satisfaction; Culture; Epidural; Companion